2013
DOI: 10.1177/0884533613508435
|View full text |Cite
|
Sign up to set email alerts
|

The Academy of Nutrition and Dietetics/The American Society for Parenteral and Enteral Nutrition Consensus Malnutrition Characteristics

Abstract: Malnutrition in adult hospitalized patients has been a significant issue for almost 40 years. Changes in 2007 to the diagnosis related groups reimbursement methodology, as outlined by the Center for Medicare and Medicaid Services, provided an impetus to improve the diagnosis and documentation of malnutrition in adult patients. Being able to accurately assess, diagnose, and document malnutrition has been challenged by the lack of a standard malnutrition definition. In 2012 a workgroup of the Academy of Nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 30 publications
2
84
0
2
Order By: Relevance
“…Interestingly, Kyle et al found similar sensitivity, specificity, and agreement for the NRS 2002 as confirmed using the Subjective Global Assessment when compared with the results that we report for the NRS 2002 . Current guidelines for the nutrition assessment as part of the nutrition care process use the 6 malnutrition clinical characteristics developed by AND/ASPEN . Given these similar results, the current study contributes to the evidence base that the nutrition assessment and NFPE, which employs the 6 malnutrition clinical characteristics outlined by AND/ASPEN, produces similar results as a nutrition assessment tool when compared with the Subjective Global Assessment.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, Kyle et al found similar sensitivity, specificity, and agreement for the NRS 2002 as confirmed using the Subjective Global Assessment when compared with the results that we report for the NRS 2002 . Current guidelines for the nutrition assessment as part of the nutrition care process use the 6 malnutrition clinical characteristics developed by AND/ASPEN . Given these similar results, the current study contributes to the evidence base that the nutrition assessment and NFPE, which employs the 6 malnutrition clinical characteristics outlined by AND/ASPEN, produces similar results as a nutrition assessment tool when compared with the Subjective Global Assessment.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, they were found to have higher rates of readmission or require ongoing services such as home healthcare following discharge [11]. Hence, due to the recognition of the importance of the impact of malnutrition on economic burden, the Centers for Medicare and Medicaid Services (CMS) have implemented a change in their reimbursement rates according to its severity [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Inspection and palpation of muscles and skinfolds can yield important information about muscle and fat stores. 26,27 Edema and ascites are associated with alterations in total body water, protein synthesis and transport, or hypoalbuminemia and should be noted if present. An evaluation for signs and symptoms of micronutrient and mineral deficiencies should be made (see Table 2 50 TOPICS IN CLINICAL NUTRITION/JANUARY-MARCH 2015 for examples).…”
Section: Physical Examinationmentioning
confidence: 99%
“…Requirement calculations should be done using estimated dry weight in edematous patients. 26 Accurate determination of dry weight is difficult in the ICU setting. Weight of retained fluid is estimated to be 2.2 kg for minimal ascites, 6 kg for moderate ascites and 14 kg for severe ascites.…”
Section: Body Composition and Anthropometrymentioning
confidence: 99%
See 1 more Smart Citation